DEVELOPMENT OF A WEB-BASED BATAK SIMALUNGUN REGIONAL LANGUAGE CORPUS USING THE RAPID APPLICATION DEVELOPMENT METHOD - Nanda, Agus Estepen; Rantung, Vivi P; Santa, Kristofel (Jurnal Teknik Informatika (Jutif), 2024)
The development of information technology has had a big influence on regional languages. Corpus data stored digitally will be very important in the future. One of the benefits of using corpus data in language analysis is that it can facilitate the process of identifying the most commonly used words or phrases in a language. Currently there are no data analysis results from the Simalungun Batak language corpus that can be utilized by the observers and there is a lack of research on the Simalungun Batak language corpus. This research aims to preserve and increase the resources of the Simalngun Batak language which is implemented in developing a web-based corpus of the Simalungun Batak regional language using the rapid application development method and can later be used by the Pekamus to compile a Simalungun Batak language dictionary. The final result is a website that can analyze the Simalungun regional language and with this website, the observers will easily analyze words from the Batak Simalungun regional language.